Maintaining service quality: Examining the impact of the HESQUAL scale on student satisfaction in HEIs - Pramono, Suwito Eko; Yulianto, Arief; Wijaya, Angga Pandu; Nasrun, Nasrun; Plangsorn, Boonrat (Association for Scientific Computing Electrical and Engineering(ASCEE), 2025)
This study aims to examine the effect of service quality and technology support on student satisfaction through student perceived value. Research in Indonesia has yet to extensively investigate service quality in the education sector using the Higher Education Service Quality (HESQUAL) framework, which provides a more accurate measurement for higher education settings. Previous studies have often utilized SERVQUAL indicators, which are not fully suitable for evaluating quality in the context of higher education institutions (HEIs). Moreover, the role of technology support in shaping student perceived value within HEIs has not been thoroughly explored in prior research. A quantitative approach was adopted in this study, employing a non-probability sampling method using purposive sampling. The sample consisted of 246 postgraduate students from a public university in Indonesia. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (SEM-PLS) to examine the relationships among the variables. The findings reveal that service quality, as measured by HESQUAL, has a positive and significant effect on student satisfaction, but does not significantly influence student perceived value. In contrast, technology support has a positive and significant impact on both student perceived value and student satisfaction. These results highlight the critical role of service quality in enhancing student satisfaction within HEIs. The novelty of this study lies in its application of the HESQUAL framework as a context-specific instrument for measuring service quality in higher education, thereby addressing a methodological gap in Indonesian educational research where this approach has been scarcely utilized.